2011
DOI: 10.1063/1.3635772
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Theoretical exploration of Au++H2, D2, and HD reactive collisions

Abstract: A quasi-classical study of the endoergic Au+(1S) + \documentclass[12pt]{minimal}\begin{document}${\rm H}_2(X^1 \Sigma _g^+$\end{document}H2(X1Σg+) → AuH+ (2Σ+) + H(2S) reaction, and isotopic variants, is performed to compare with recent experimental results [F. Li, C. S. Hinton, M. Citir, F. Liu, and P. B. Armentrout, J. Chem. Phys. 134, 024310 (2011)].10.1063/1.3514899 For this purpose, a new global potential energy surface has been developed based on multi-reference configuration interaction ab initio calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
(39 reference statements)
2
9
0
Order By: Relevance
“…The experimental cross section to form AuH + products presents a peak about 4.60 eV, close to the total dissociation threshold and was very nicely reproduced by QCT simulations on a new three-dimensional PES. 10 In these simulations, it was found that after 4.50 eV, the total fragmentation channel cross section increases rapidly with increasing energy, becoming dominant after 5.10 eV, and of the same order.…”
Section: Collisional Results and Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The experimental cross section to form AuH + products presents a peak about 4.60 eV, close to the total dissociation threshold and was very nicely reproduced by QCT simulations on a new three-dimensional PES. 10 In these simulations, it was found that after 4.50 eV, the total fragmentation channel cross section increases rapidly with increasing energy, becoming dominant after 5.10 eV, and of the same order.…”
Section: Collisional Results and Discussionmentioning
confidence: 80%
“…The reaction cross section for the formation of the hydride presents a maximum for the three system, as previously reported for Au + + H 2 . 10,32 The position, height, and width of the cross section strongly depends on the system, while the total dissociation channel opens at ≈4.50 eV in all cases, the dissociation energy of H 2 .…”
Section: Collisional Results and Discussionmentioning
confidence: 95%
See 3 more Smart Citations